Sustainable Photocatalytic Degradation Of Phenol Using Iron-Based Bead Catalyst - Muhammad Farhan, Hanafi; Muhamad Hafiffy, Kamaruddin; Diyana Faziha, Mohamad; Norzahir, Sapawe (Integrated Publishing Association, 2025)
The increasing industrial reliance on phenol has led to a significant rise in phenolic pollution, necessitating effective and sustainable treatment methods. In this study, a nanocomposite iron bead catalyst was synthesized and evaluated for the photocatalytic degradation of phenol in aqueous solution. The degradation performance was assessed under varying conditions, including pH levels (3, 5, 7, 8, 9, and 11), cat alyst dosages (10, 20, 30, 40, and 50 g/L), and initial phenol concentrations (10, 20, 30, 40, 70, and 100 ppm). UV-Vis spectrophotometry was employed to determine phenol removal efficiency over a reaction time of 3 hours. The functional groups and structural features of the iron bead catalyst were characterized using FTIR spectroscopy, revealing a strong absorption band at 570.36 cm⁻¹ corresponding to the Fe–O stretching vibration in Fe₃O₄, confirming the presence of magnetite nanoparticles. Additional bands between 500–700 cm⁻¹ were attributed to Fe–O bonds in iron oxide structures. The optimal degradation condition was achieved at pH 3, with a catalyst dosage of 40 g/L and an initial phe nol concentration of 10 ppm, resulting in a 95% removal efficiency at room temperature within 3 hours. The simple a nd time-efficient synthesis of the iron bead catalyst, coupled with its excellent degradation performance, demonstrates its potential as a viable alternative to conventional phenol removal methods.